Infer#’s journey to bring Infer to the .NET world - Shi, Xin; Liu, Xiaoyu; Jin, Matthew; Sundaresan, Neel (PLDI 2022, 2022)
Inter-procedural static analysis is almost nonexistent in the .NET space. By leveraging Infer’s capabilities, Microsoft’s Infer# fills such gap. With close collaboration with Meta, we have made tremendous progress in terms of analysis quality and performance for .NET languages such as C#, while contributing key innovations back to the Infer community. We will go through the fundamental design and architecture of Infer# which made this possible. In addition, we will share some user stories at Microsoft about how Infer# helped teams identify hard-to-find issues which caused service degradation and disruption.